Navigating NGO Sustainability: Stakeholders, Operational Efficiency, and Innovation in Floating Hospitals - Nodya Melinda Noori; Ediansyah Ediansyah; Nofierni Nofierni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to evaluate the determinants of organizational sustainability within the Doctor Peduli Foundation (doctorSHARE), specifically regarding its Floating Hospital program. Specifically, it examines the influence of stakeholder support and operational efficiency on organizational sustainability, while analyzing the role of organizational innovation as a mediating variable in ensuring the continuity of medical services in remote areas. Employing a quantitative approach with a survey method, data were collected from 81 respondents comprising staff and volunteers directly involved in the Floating Hospital's operations. Structural Equation Modeling (SEM) was utilized to analyze the data and test the proposed hypotheses.The results reveal that stakeholder support does not have a significant direct impact on either organizational sustainability or innovation performance. Conversely, operational efficiency emerged as a dominant factor with a significant positive influence. Furthermore, organizational innovation was found to play a crucial role as a mediator, strengthening the impact of operational efficiency on organizational sustainability.This study concludes that the sustainability of non-profit organizations such as doctorSHARE is determined more by management's ability to optimize internal resources efficiently and innovatively than by reliance on external support. Consequently, strengthening internal operational systems should be a primary strategic priority to ensure long-term organizational existence.